Educare al merito per promuovere l'etica della responsabilità nella scuola delle competenze - Rosaria Capobianco (Firenze University Press, 2022)
The essay, starting from the analysis of the terms: merit, meritocracy and meritoriousness, reflects on the important role of the school that must educate the new generation to be able to recognize the many traps of meritocracy. The school, in fact, must educate to meritoriousness, in order to create the society of the common good, which supplants the dichotomous society of winners and losers. Through the transversal teaching of Civic Education it is possible to promote a conscious and inclusive education on merit.